Trabecular structural difference between the superior and inferior regions of the vertebral body: a cadaveric and clinical study - Shin, Dong Eun; Lee, Younghun; An, Hyun-Ju; Hwang, Tae-Sun; Cho, Jin-Woo; Oh, Jongbeom; Ahn, Wooyeol; Lee, Jaemin; Hong, Chul Gie; Lee, Yeonju; Lee, Soonchul (Frontiers in Endocrinology, 2023)
Background: Osteoporotic vertebral compression fractures commonly involve the superior vertebral body; however, their associated causes have not yet been clearly established. This study aimed to determine the trabecular structural differences between the superior and inferior regions of the vertebral body using cadaveric and clinical studies. Materials and Methods: First, five vertebrae were collected from three human cadavers. The trabecular structures of the superior and inferior regions of each vertebral body were analyzed using micro-computed tomography (micro-CT), finite element analysis (FEA), and biomechanical test. Based on the results of the ex vivo study, we conducted a clinical study. Second, spine CT images were retrospectively collected. Bone volume and Hounsfield unit were analyzed for 192 vertebral bodies. Finally, after sample size calculation based on the pilot study, prospectively, 200 participants underwent dual-energy X-ray absorptiometry (DXA) of the lateral spine. The bone mineral densities (BMDs) of the superior and inferior regions of each lumbar vertebral body were measured. The paired t-test and Wilcoxon signed-rank test were used for the statistical analyses, and p-value < 0.05 was considered significant. Results: Cadaver studies revealed differences between the superior and inferior trabecular bone structures. The bone volume ratio, BMD, and various other trabecular parameters advocated for decreased strength of the superior region. Throughout the biomechanical study, limitations of the compression force were 3.44 and 4.63 N/m2 for the superior and inferior regions, respectively. In the FEA study, the inferior region had a lower average displacement and higher von Mises stress than the superior region. In the clinical spine CT-based bone volume and BMD study, the bone volume was significantly higher in the inferior region than in the superior region. In the lateral spine DXA, the mean BMD of the superior region of vertebral bodies was significantly lower compared with that of the inferior region. Conclusions: The superior trabecular structure of the lumbar vertebral bodies possesses more biomechanical susceptibility compared with the inferior trabecular structure, confirming its dominant role in causing osteoporotic vertebral fractures. Physicians should also focus on the BMD values of the superior region of the vertebral body using lateral spine DXA to evaluate osteoporosis.